Effect of Compressive Strain Rate on Microstructure and Mechanical Properties of 7050 Aluminium Alloy. (8th December 2021) - Shen, Qiang; Huang, Luochuang; Li, Yan; Yu, Kang; Liu, Dezheng
Abstract : 7050 aluminium alloy is a superior material used in the areas of aerospace and automobile manufacturing. In this work, homogeneous cast cylinder samples of 7050 aluminium alloy with size of Φ80 mm × 100 mm were compressed isothermally at 350°C with compressive strain rate of 0.1 s −1, 1 s −1, and 10 s −1, respectively. The samples were then processed into standard tensile specimens, and then tensile testing was done by using the GL8305 universal testing machine. The grain sizes and fracture morphology were analyzed by the SEM observation and cellular automaton (CA) method. The effect of compressive strain rate on microstructure and mechanical properties of 7050 aluminium alloy was investigated. The results show the following. (1) Grain refinement occurred after compression. The grain sizes of the samples decrease with the decrease of compressive strain rate. The grain sizes in the radial edge and the axial center of the cylinder samples are the smallest. (2) The tensile strength and breaking elongation rate were improved when compared to the original alloy. The mechanical properties of samples compressed with compressive strain rate of 0.1 s −1 are the best. (3) The fracture morphology of the samples shows that the fracture of the samples is ductile fracture. The sizes and depths of dimples increased with the decrease of grain sizes.